An Observational Study to Compare the Effects of Esmolol and Diltiazem in Attenuating the Haemodynamic Response to Laryngoscopy and Endotracheal Intubation (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background - Laryngoscopy and endotracheal intubation are two most essential part of anaesthetic management. They help in control of airway during general anaesthesia and produce transient marked sympathetic response which manifest as an increase in heart rate, blood pressure, intraocular and intracranial pressure. Esmolol is a selective beta adrenergic receptor antagonist and diltiazem is a calcium channel blocker. The drugs were compared towards reducing the haemodynamic stress response.Methods –This study included 50 patients of both gender, with ASA grade I to IV, aged between 18 to 60 years, scheduled for surgery under general anaesthesia. Among these 25 patients were given inj. esmolol with dose of 1mg/kg i.v.bolus and 25 patients were given inj. diltiazem with dose of 0.2mg/kg i.v.bolus . The haemodynamic parameters were recorded at baseline , just after premedication , after injecting the drug under study, after intubation at 1 , 3 , 5 and 10 minutes. Conclusion –Patients who received inj. esmolol in dose 1mg/kg i.v. showed marked attenuation in both heart rate as well as systolic and diastolic blood pressure whereas inj. diltiazem with dose of 0.2mg/kg only showed attenuation in systolic and diastolic blood pressure but failed to achieve any control over heart rate.
Keywords: Diltiazem, Esmolol, Intubation , Laryngoscopy